Money for nothing? Universal child care and maternal employment - Tarjei Havnes; Magne Mogstad (University of Oslo, Department of Economics, 2009)
The strong correlation between child care and maternal employment rates has led previous research to conclude that affordable and readily available child care is a driving force both of cross-country differences in maternal employment and of its rapid growth over the last decades. We analyze the introduction of subsidized, universally accessible child care in Norway. Our precise and robust difference-in-differences estimates reveal that there is little, if any, causal effect of child care on maternal employment, despite a strong correlation. Instead of increasing mothers' labor supply, the new subsidized child care mostly crowds out informal child care arrangements, suggesting a significant net cost of the child care subsidies.
Keywords: J13; H40; J21; 330; universal child care; female labor force participation; Kinderbetreuung; Frauenerwerbstätigkeit; Arbeitsangebot; Mütter; Norwegen